Emerging Targets for Developing T Cell-Mediated Vaccines for Human Immunodeficiency Virus (HIV)-1 - Wijesundara, Danushka K.; Ranasinghe, Charani; Grubor-Bauk, Branka; Gowans, Eric J. (Frontiers in Microbiology, 2017)
Human immunodeficiency virus (HIV)-1 has infected >75 million individuals globally, and, according to the UN, is responsible for 2.1 million new infections and 1.1 million deaths each year. Currently, there are 37 million individuals with HIV infection and the epidemic has already resulted in 35 million deaths. Despite the advances of anti-retroviral therapy (ART), a cost-effective vaccine remains the best long-term solution to end the HIV-1 epidemic especially given that the vast majority of infected individuals live in poor socio-economic regions of the world such as Sub-Saharan Africa which limits their accessibility to ART. The modest efficacy of the RV144 Thai trial provides hope that a vaccine for HIV-1 is possible, but as markers for sterilizing immunity are unknown, the design of an effective vaccine is empirical, although broadly cross-reactive neutralizing antibodies (bNAb) that can neutralize various quasispecies of HIV-1 are considered crucial. Since HIV-1 transmission often occurs at the genito-rectal mucosa and is cell-associated, there is a need to develop vaccines that can elicit CD8+ T cell immunity with the capacity to kill virus infected cells at the genito-rectal mucosa and the gut. Here we discuss the recent progress made in developing T cell-mediated vaccines for HIV-1 and emphasize the need to elicit mucosal tissue-resident memory CD8+ T (CD8+ Trm) cells. CD8+ Trm cells will likely form a robust front-line defense against HIV-1 and eliminate transmitter/founder virus-infected cells which are responsible for propagating HIV-1 infections following transmission in vast majority of cases.